EVALUATION OF TORA SCHEME AND SOCIAL FORESTRY PROSPECTS IN RESOLVING TENURE CONFLICTS IN OLD VILLAGES AND COMMUNITY PLANTATIONS WITHIN FOREST AREAS: A CASE STUDY OF THE STATE OF PETAPAHAN, KAMPAR REGENCY, RIAU PROVINCE - Devi Novita Simanungkalit; Gloria Ammelia Sinaga; Senja Purnama; Rumiyanti Sitohang; Dorma Ulina Girsang (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to evaluate the effectiveness of the Agrarian Reform Object Land (TORA) scheme and analyze the prospects of Social Forestry in resolving tenure conflicts in Petapahan State, Kampar Regency, Riau Province. This study uses a qualitative descriptive approach with a case study in the State of Petapahan. Data were obtained from policy documents, academic publications, NGO reports, and verified media, then analyzed using the policy gap analysis approach. The results show that although the 251-hectare Imbo Putui Customary Forest has been formally recognized in 2020, substantive protection is still weak as approximately 167 hectares have been encroached upon by oil palm plantationscon. In addition, about 13,000 hectares of community gardens are still under HTI concessions without land certificates. These findings show that the institutional dualism between agrarian law and forestry law is the main obstacle in resolving tenure conflicts. This research contributes to the study of agrarian reform and forestry governance by showing that institutional fragmentation between the agrarian and forestry systems limits the effectiveness of the implementation of TORA and Social Forestry. This study recommends participatory mapping, settlement of concession boundaries, strengthening community institutions, and integrated implementation of the One Map Policy to achieve sustainable and equitable conflict resolution. This study only focuses on the case of the State of Petapahan so that the results of the study have limitations in generalization in other regions with different socio-political conditions.